Development of a solar dryer for spent coffee grounds for biodiesel production - Angeles, Javier Alfonso R. (Animo Repository, 2021)
The world consumes 10 million tons of coffee which leaves a waste product called spent coffee grounds (SCG). Typically, SCG is sent to landfills which could be harmful to the environment when improperly disposed of. With this, SCG has become an excellent source for biodiesel production after being treated. In this paper, the researchers were able to design, fabricate, and test a dryer for SCG and study its drying kinetics. Using the best setup, cabinet temperature reached 45℃ and was able to increase the humidity by 47.7%. Its performance was verified through energy analysis, statistical methods, and a two full factorial design wherein ANOVA was used to predict the average cabinet temperature and average drying rate. A mathematical model fitted in Newton’s drying kinetics model was developed to describe the drying behavior of SCG. Inside the drying cabinet the heat loss reached a maximum of 1.97 W due to a lack of insulation of the walls of the chamber. Thermal efficiencies were also found ranging from 5.8% up to 15.7% for the different treatments with the low efficiency being attributed to the small quantity of mass amounting to only 100 grams of SCG used during drying.